(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2022)
The Journal @limentech, Food Science and Technology has projected the present volume 20 No. 1 of the year 2022 to make known to the scientific community the research results of different University Education Institutions, public and private. The topics published in this volume cover contents of interest to the agri-food sector: biotechnology, food engineering and technology with advances in the development of innovative bakery products. Finally, we extend an invitation to the scientific community to continue researching and disseminating their results by publishing in our Journal @limentech, through the Open Journal platform or directly to the institutional email of the Journal @limentech and also thank the commitment and participation of the active members of the Scientific Committee, and referees evaluators of the articles submitted, for their contributions and commitment to the scientific community of Food Science and Technology.